2016
DOI: 10.1016/j.seizure.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the serum cytokine levels before and after adrenocorticotropic hormone (ACTH) therapy in patients with infantile spasm

Abstract: Our study supports the recent idea that IL-6 and IL-17A are cytokines involved in the pathogenesis of infantile spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…[2,10] IL-2 and TNF-α are the main cytokines that are involved in inflammation and have recently been associated with infantile spasm. [3] Liu et al [6] revealed that the expression levels of IL-2 are higher in patients with WS than in controls. IL-2 is secreted by activated CD4 + T cells and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,10] IL-2 and TNF-α are the main cytokines that are involved in inflammation and have recently been associated with infantile spasm. [3] Liu et al [6] revealed that the expression levels of IL-2 are higher in patients with WS than in controls. IL-2 is secreted by activated CD4 + T cells and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Previous studies have shown that immunomodulatory dysfunction in humoral immunology and cytokine levels in patients with WS. [3] Patients with the clinical feature of epileptic spasms have higher levels of antibodies against the N-methyl-d-aspartate-type glutamate receptor in the cerebrospinal fluid. [4] The levels of serum immunoglobulins (Igs) and complement proteins of IgA, IgM, IgG, C3, and C4 have been found to be lower in patients with WS than in control patients.…”
Section: Introductionmentioning
confidence: 99%
“…Here we show that the complement C5ar1 receptor antagonist, PMX53, also reduced spasms, suggesting contribution of the innate inflammatory system, represented by C5a, to IS. The involvement of the inflammatory system in IS was recently documented by the increase of cytokines IL6 and IL17A in patients with IS prior to treatment initiation compared to healthy individuals 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these levels decreased after ACTH treatment, the change was not significant. 12 In our previous study, post-treatment blood sampling was performed within 1 week after symptom improvement. However, Shiihara and Türe performed blood sampling after 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of cytokine levels in West syndrome patients before and after ACTH treatment are limited. [10][11][12] To our knowledge, a serial analysis of the responses of multiple inflammation-related mediators to ACTH in patients with West syndrome has not previously been reported. This study aimed to explore the mechanisms of ACTH action by evaluating various cytokine responses to ACTH in patients with West syndrome.…”
mentioning
confidence: 96%